Growth And Biochemical Composition Of Isochrysis Maritima Billard And Gayral 1972 Under Photoautotrophic And Heterotrophic Conditions : Assessment For Aquaculture Feed - Eshak, Mohammad Basri (2016)
The effects of photoautotrophic and heterotrophic conditions on growth and biochemical composition of isochrysis maritima, isolated from teluk aling, penang were investigated. Under photoautotrophic condition, i. Maritima was cultivated in different nitrogen sources (nitrate, nitrite, and urea) and harvested at different growth phases (exponential, early stationary and late stationary) to examine the impact of nitrogen sources and growth phases on growth and biochemical composition. The results revealed that urea at late stationary was the most suitable nitrogen source, which recorded high cell growth (10.9 ± 0.63 x 106 cell.Ml'1) and biochemical composition including protein (32.1 ± 3.17%), carbohydrate (37.0 ± 0.36%) and fatty acids content (total sfa = 32.92 ± 2.59 %; total mufa = 6.26 ± 0.83%; total pufa = 15.55 ± 1.49%) and was further investigated onto higher volume of walne’s medium (50 l). Under heterotrophic condition, i. Maritima was cultivated in different organic carbon sources (glucose, sucrose, lactose, fructose and sodium acetate) at different concentrations (0.02 m, 0.05 m and 1.0 m) with urea as nitrogen source to determine the suitable carbon sources and concentrations to maximize the growth of this strain.